Adolescent social isolation shifts the balance of decision-making strategy from goal-directed action to habitual response in adulthood via suppressing the excitatory neurotransmission onto the direct pathway of the dorsomedial striatum. (6th May 2022) - Shan, Qiang; Yu, Xiaoxuan; Tian, Yao
Abstract: Adverse experience, such as social isolation, during adolescence is one of the major causes of neuropsychiatric disorders that extend from adolescence into adulthood, such as substance addiction, obsessive–compulsive disorder, and eating disorders leading to obesity. A common behavioral feature of these neuropsychiatric disorders is a shift in the balance of decision-making strategy from goal-directed action to habitual response. This study has verified that adolescent social isolation directly shifts the balance of decision-making strategy from goal-directed action to habitual response, and that it cannot be reversed by simple regrouping. This study has further revealed that adolescent social isolation induces a suppression in the excitatory neurotransmission onto the direct-pathway medium spiny neurons of the dorsomedial striatum (DMS), and that chemogenetically compensating this suppression effect shifts the balance of decision-making strategy from habitual response back to goal-directed action. These findings suggest that the plasticity in the DMS causes the shift in the balance of decision-making strategy, which would potentially help to develop a general therapy to treat the various neuropsychiatric disorders caused by adolescent social isolation. Such a study is especially necessary under the circumstances that social distancing and lockdown have caused during times of world-wide, society-wide pandemic.